(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
The use of indigenous game-based activities in teaching Physics concepts can eradicate the continuous perception of students that Physics is a boring and difficult subject. This study focused on the development and validation of indigenous game-based activities (IGBA) that can be used as a springboard to teach Physics concepts and enhance the performance of students. It used the Research and Development methodology that includes the validation of the indigenous game-based activities and try-out wherein the researcher used one-group pretest-posttest design to 42 purposively-selected students in a public secondary school in eastern Ilocos Norte, Philippines. Using a researcher-made and item-analyzed pretest and posttest, an adapted students’ views checklist, interview guide and adapted validation tool, the study found out that Ilocos Norte has a lot of indigenous games rich with Physics concepts, using games familiar to students encourages better participation among learners and solicits greater interest towards the subject, thus making the teaching-learning process more appealing to students. The purposively selected teachers strongly agreed that the IGBA is a valid instructional material for teaching Physics concepts. Tryout results show that the material effectively improves students’ performance in Physics. It was supported by students’ views that when the activities are used in teaching, Physics becomes interesting, motivating, challenging, enjoyable and full of fun, not difficult to learn and understand because they are applicable and relevant, not time consuming because they ease students’ burden in problem-solving, elicit maximum participation among learners, and ensure greater retention of the concepts they learn.